Enhancement of Cholinesterase Inhibition of Alpinia galanga (L.) Willd. Essential Oil by Microemulsions - Chaiyana, Wantida; Sriyab, Suwannee; Okonogi, Siriporn (Molecules (Basel, Switzerland), 2022)
This study aimed to investigate the chemical composition and reveal the selective inhibitory activity of Alpinia galanga (L.) Willd. essential oil (AGO) on acetylcholinesterase (AChE) compared to butyrylcholinesterase (BChE). The chemical composition of AGO was investigated by means of gas chromatography–mass spectrometry. Ellman’s method was used to determine the inhibitory activities against AChE and BChE. Microemulsion systems with desirable anticholinesterase effects were developed. Methyl cinnamate and 1,8-cineole were reported as the major component of AGO. The IC50 values of A. galanga oil against AChE and BChE were 24.6 ± 9.6 and 825.4 ± 340.1 µg/mL, respectively. The superior selectivity of AGO on AChE (34.8 ± 8.9) compared to galantamine hydrobromide (6.4 ± 1.5) suggested AGO to be an effective ingredient with fewer side effects for Alzheimer’s treatment. Interestingly, the microemulsion of AGO possessed significantly higher anticholinesterase activity than that of native oil alone. Therefore, microemulsion of AGO is a promising alternative approach for the treatment of Alzheimer’s disease.